Alt Lit, Illuminati Girl Gang and Porn Carnival: A Decade of Online Poetry Communities (2010-2020) - Laura Marie Marciano (Sillages Critiques)
The kind of twenty-first-century poetry that contains the language of late capitalism, products and brands, and resembles the syntax of text messaging, Instagram comments and memes, is a result of the collective rhetoric of a Millennial group of writers that came of age on the Internet. Online communities and publications that emerged between 2010 and 2016 such as Alt Lit, Internet Poetry, Illuminati Girl Gang, and others, have in fact paved the way for provocative multimodal poetry books such as Rachel Rabbit White’s Porn Carnival (2019). These groups of writers, now many in their early to mid-thirties, are the founders of new digital discourse communities, online journals, and digital reading series, which experienced renewed relevance during the Covid-19 crisis when in-person readings were not possible. This paper discusses the aesthetic and social effects of online discourse communities on the production of poetry books, emphasizing how digital communities function as a continuous and collective writing project on their own.